2022
DOI: 10.3389/fcell.2022.1069064
|View full text |Cite
|
Sign up to set email alerts
|

Cyclins and CDKs in the regulation of meiosis-specific events

Abstract: How eukaryotic cells control their duplication is a fascinating example of how a biological system self-organizes specific activities to temporally order cellular events. During cell cycle progression, the cellular level of CDK (Cyclin-Dependent Kinase) activity temporally orders the different cell cycle phases, ensuring that DNA replication occurs prior to segregation into two daughter cells. CDK activity requires the binding of a regulatory subunit (cyclin) to the core kinase, and both CDKs and cyclins are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 160 publications
0
2
0
Order By: Relevance
“…The housekeeping gene β‐Actin was used as a reference for normalization. Cyclins and CDKs play essential roles in cell cycle progression, and their complex acts as a protein kinase to initiate specific cell‐cycle processes [55] . CDKs are critical in regulating cell division by modulating the transcription process in response to various extracellular and intracellular signals [56] …”
Section: Resultsmentioning
confidence: 99%
“…The housekeeping gene β‐Actin was used as a reference for normalization. Cyclins and CDKs play essential roles in cell cycle progression, and their complex acts as a protein kinase to initiate specific cell‐cycle processes [55] . CDKs are critical in regulating cell division by modulating the transcription process in response to various extracellular and intracellular signals [56] …”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that GLP-1 suppressed the proliferative activity of preadipocytes. Cell proliferation is influenced by numerous cell cycle regulators, with cyclin D1 and D2 (D3 is not expressed during mitotic clonal expansion), and their catalytic partners, cyclin dependent kinases, playing a pivotal role in cell cycle progression ( Reichart and Eick, 1999 ; Ide et al, 2011 ; Palacios-Blanco and Martín-Castellanos, 2022 ). The present study observed a significant downregulation of cyclin D1 in response to liraglutide.…”
Section: Discussionmentioning
confidence: 99%